Musiktherapie bei erwachsenen CI-Trägern: Effekte auf die Musikwahrnehmung und die subjektive Klangqualität = Music therapy in adults with cochlear implants : effects on music perception and subjective sound quality - Hutter, Elisabeth; Grapp, Miriam; Argstatter, Heike (HNO, 2016)
BackgroundPeople with severe hearing impairments and deafness can achieve good speech comprehension using a cochlear implant (CI), although music perception often remains impaired. A novel concept of music therapy for adults with CI was developed and evaluated in this study.MethodsThis study included 30 adults with a unilateral CI following postlingual deafness. The subjective sound quality of the CI was rated using the hearing implant sound quality index (HISQUI) and musical tests for pitch discrimination, melody recognition and timbre identification were applied. As a control 55 normally hearing persons also completed the musical tests.ResultsIn comparison to normally hearing subjects CI users showed deficits in the perception of pitch, melody and timbre. Specific effects of therapy were observed in the subjective sound quality of the CI, in pitch discrimination into a high and low pitch range and in timbre identification, while general learning effects were found in melody recognition.ConclusionMusic perception shows deficits in CI users compared to normally hearing persons. After individual music therapy in the rehabilitation process, improvements in this delicate area could be achieved.